Enhancing ICT for productivity in Sub-Saharan Africa: Thresholds for complementary policies - Simplice Asongu; Paul N. Acha-Anyi (African Governance and Development Institute (AGDI), 2020)
The purpose of this research is to investigate the relevance of enhancing information and communication technology (ICT) on dynamics of total factor productivity (TFP) in 25 Sub-Saharan African countries using data covering the period 1980-2014. The empirical evidence is based on the Generalised Method of Moments. The following main findings are established. First, while enhancing ICT overwhelmingly has net positive effects on productivity, the corresponding marginal effects are negative. Second, anextended analysis is performed to establish thresholds for complementary policies. These thresholds are: 100 % mobile phone penetration for TFP; between 101.214 % and 101.419 % mobile phone penetration for welfare TFP and 15 % internet penetration for welfare real TFP. It follows that approximately 100% mobile penetration and 15% internet penetration are thresholds at which ICT should be complemented with other macroeconomic policies for favorable outcomes on productivity dynamics. Other policy implications are discussed.
Keywords: E23; F21; F30; L96; O55; 330; Productivity; Information Technology; Sub-Saharan Africa